Thursday
March 30, 2017

Post a New Question

Posted by on .

ok so having trouble with this have tried and trie but can seeem to come up with tthe answer. d/(1-d)^2=(d+1)^2 - 1/d

the answer we were given is d^5-2d^3-2d^2+3d-1=0

  • Math - ,

    d/(1-d)^2=(d+1)^2 - 1/d
    the LCD = d(1-d)^2
    so multiply each term by that

    d^2 = d(1-d)^2 (d+1)^2 - (1-d)^2
    d^2 + (1-d)^2 = d[(1-d)(1+d)]^2
    d^2 + (1-d)^2 = d[(1-d^2]^2
    d^2 + 1 - 2d + d^2 = d(1 - 2d^2 + d^4)
    d^2 + 1 - 2d + d^2 = d - 2d^3 + d^5
    d^5 - 2d^3 - 2d^2 + 3d - 1 = 0 as shown in your answer

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question